Rocky Flats: a case study of nuclear contamination, knowledge, and environmental justice - Luxton, India M., author; Malin, Stephanie, advisor; Hall, Peter, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2017)
This thesis seeks to examine the environmental and public health experiences of individuals who live(d) near the Rocky Flats Nuclear Facility in Arvada, Colorado during and after its operation. The data presented for this thesis has been collected as part of MSU-CSU's Rocky Flats Health Study to collect qualitative interview data from individuals who suffer from rare cancers, chronic illnesses, or have had a family member who has passed due to these health outcomes. Currently, there are few health studies related to Rocky Flats Nuclear Weapons Plant, and those that do exist are highly contested (Iversen 2012). In addition to archival analysis of fifteen interviews, oral histories were conducted with fifteen individuals. Oral histories illustrate community perceptions of Rocky Flats, as well as the impact of living in close proximity has had on their health and quality of life. In my findings, I illustrate the political, institutional, and interpersonal aspects of accessing information regarding environmental contamination and subsequent health risks. Findings illustrate that access to information both during and after the facility's operation was severely constrained by structural barriers, conflicting reports of safety, and a culture of secrecy surrounding the site. Additionally, I examine the contested nature of participants' illnesses as well as their notions of justice. Understanding the lived, psycho-social experiences of people with contested illness is critical to connecting questions of justice and environmental contamination.